True crime Japan thieves, rascals, killers, and dope heads : true stories from a Japanese courtroom - Murphy, Paul 1968- (Tuttle Publishing, 2016)
"A middle-aged carpenter beats his 91-year old mother to death and goes to work the following day, leaving the body for his wife to find. An 82-year old woman is jailed for 10 months for stealing fried chicken. Like nearly all defendants in Japan, they both plead guilty. What happens between plea and sentencing is the subject of True Crime Japan. In this fascinating crime book journalist and longtime Japan resident Paul Murphy provides a glimpse of Japanese society through a year's worth of criminal court cases in Matsumoto, a city 140 miles to the west of Tokyo. The defendants in these cases range from ruthless mobsters to average citizens, often committing similar crimes in rather different ways, and for different reasons. Based on court hearings and interviews with the defendants, their families, neighbors and lawyers--Murphy explores not only the motives of offenders, but the culture of crime and punishment in Japan. The resulting true crime book provides a lens through which to view this honor-shame based, conformist culture, and shows how, in its role within that culture, the court system reveals Japan to be, surprisingly to some, a land of true individuals"--Provided by publisher.